Four-armed portrayal of Bhairav - Temples of India Project Team (Jio Institute, 2024)
The only significant depiction of the divinity of Shiva is found in the form of a four-armed portrayal of Bhairav on a temple shaft near the entrance of the temple, within the mandapa. It is the first religious image encountered upon visiting the temple. He is adorned with a serpent necklace, but other identifying attributes have deteriorated over time. His heavily bejewelled naked body reveals his genitalia.